Robust, multiscale liquid-metal patterning enabled by a sacrificial sealing layer for flexible and wearable wireless powering. Issue 48 (20th November 2019) - Teng, Long; Zhu, Lifei; Handschuh-Wang, Stephan; Zhou, Xuechang
Abstract : A robust patterning method was developed for the fabrication of liquid metal patterns toward flexible and wearable wireless powering. Abstract : Patterning of liquid metals (LMs) at different length scales remains one of the issues hindering their practical applications. Herein, we report a robust LM patterning method enabled by transiently sealing and subsequently dissolving a sacrificial layer (a polyvinyl alcohol (PVA) thin film or an adhesive tape). In this method, the LM was filled into the channels, which were temporarily formed by sealing with a sacrificial layer, by either negative or positive pressure. Afterward, LM patterns were obtained by the dissolution of the sacrificial layer in water. This method affords a robust generation of micro- and macro-patterns of LMs in a wide range from 30 μm to 1200 μm with high reliability. To demonstrate the potential application of this method, flexible and wearable LM-based wireless charging devices were fabricated, optimized and characterized. A power transfer efficiency (PTE) up to 60% was achieved while maintaining their function even at a bending radius of 12.5 mm. As a proof-of-concept, flexible LM-based wireless charging devices were employed to power passive, implantable and wearable devices.